Emergency and Trauma of Hand and Wrist - Kraan, Rik B.; Walstra, Frances E.; Teunis, Teun; Smithuis, Frank; Van Dijke, Cornelis F.; Maas, Mario (Seminars in Musculoskeletal Radiology, 2017)
Traumatic injuries of the hand and wrist are common in daily practice. Several challenges arise in the process of diagnosis and guiding the clinician. Knowledge of the complex finger, hand, and wrist anatomy is essential to understand the broad array of traumatic injuries extending from (stress)fractures to ligament, tendon, and neurovascular injuries. This article provides an overview of the different imaging techniques used in the evaluation of the hand and wrist. Emphasis is placed on the most common traumatic injuries of the hand, wrist, and fingers, and the imaging modality of choice in evaluating these injuries.
Keywords: trauma; hand; wrist; fingers; musculoskeletal radiology